Sustainable energy saving alternatives in small buildings. (April 2019) - Sher, Farooq; Kawai, Aiki; Güleç, Fatih; Sadiq, Hamad
Abstract: Day lighting significance in architectural designs is well established for enhancing visual comfort, energy-efficiency and low carbon buildings development. Practising the atrium element in the modern architectures has been increasingly popular in recent years because of the fact that the transitional space with good environmental elements can improve the quality of the buildings and reduce extra energy utilisation. The present study explores the advantages and effectiveness of the atrium on the energy performance of small buildings, a case study of 'The Azuma Row House'. Based on local micro-climate data Autodesk Ecotect Analysis was performed to calculate the daylight factors and the energy demand of the building. A comparison was made with atrium and without atrium in the building to evaluate overall energy savings. The results show a higher annual heating energy demand with atrium 3443 kWh compared without atrium 2526 kWh. The annual cooling energy demand without atrium 2516 kWh is significantly greater than with atrium 912 kWh. The total energy requirements under no atrium case is about 5042 kWh which is considerably higher than the total annual energy demand with atrium 4355 kWh. The total amount of energy saved is about 15.7% per year by introducing the sunlight through the atrium. Along with the increasing issue of the energy crisis, environmental problem and the beautiful design of atrium, the development of atrium in modern architecture designing is feasible to have a good future.